Omicron, a new SARS-CoV-2 variant: assessing the impact on severity and vaccines efficacy - Gaurav Joshi; Ramarao Poduri (Taylor & Francis Group, 2022)
The reply letter has been put forth in response to the comment made by Karthyayani Priya Satish entitled "India and the COVID-19 Vaccine." The comment was made in context to our published work "Exploring the covid-19 vaccine candidates against SARS-CoV-2 and its variants: where do we stand and where do we go?" The reply letter is concerned with the newer variant of SARS-CoV-2, i.e., Omicron and its impact on severity and vaccine efficacy. Though the variant is mild, as per the reports, the cases are rising at an unprecedented rate that may create havoc on humankind considering shortages of RT-PCR testing and prevailing unequal vaccine distribution and vaccine hesitancy.